The right to science: then and now - Porsdam, Helle; Mann, Sebastian Porsdam (Cambridge University Press, 2022)
Introduction / Helle Porsdam and Sebastian Porsdam Mann -- The dawning of a right : science and the Universal Declaration of Human Rights (1941-1948) -- The origins of the right to science : the American Declaration on the Rights and Duties of Man -- IP rights & human rights : what history tells us and why it matters -- Fostering a love of truth : conceptions of science in UNESCO's early years -- The right to science and the evolution of scientific integrity -- On the right to science as a cultural human right -- Mainstreaming science and human rights in UNESCO -- Considering the right to enjoy the benefits of scientific progress and its applications as a cultural right : a change in perspective -- Implications of the right to science for people with disabilities -- Science in the times of SARS-CoV-2 -- "Fight the fear with the facts!" -- The right to science - From principle to practice and the role of national science academies -- The right to science in practice : a proposed test in four stages -- The right to science : a practical tool for advancing global health equity and promoting the human rights of people with tuberculosis -- A proposal for indicators of the human right to science -- Epilogue : tensions in the right to science then and now.